PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA SDN 024 LIMAU MANIS - Nur Asnia; Afriza Rahma Rani; Masrul; Muhammad Syahrul Rizal; Melvi Lesmana Alim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low writing skills of students at SDN 024 Limau Manis. One solution to overcome this problem is to use a cooperative learning model of Cooperative Integrated Reading and Composition (CIRC) type. The purpose of this study was to describe the improvement of writing skills by using the CIRC type cooperative model of SDN 024 Limau Manis students. This research method is Classroom Action Research (PTK) which consists of two cycles. Each cycle consists of two meetings and four stages, namely, planning, implementation, observation, and reflection. The subjects of this research were fourth grade students of SDN 024 Limau Manais. Data collection techniques were tests, observation, and documentation. The results of this study can be concluded that students' writing skills in the pre-action 54.46, in cycle I increased to 73.21 and in cycle II to 84.82. The increase in the percentage of students who reached the KKM in writing in the pre-action condition 28.57%, cycle I 57.14%. and cycle II increased to 71.42%. Thus it can be concluded that using the CIRC type cooperative learning model can improve the writing skills of grade IV students of SDN 024 Limau Manis